Pengaruh Kombinasi Mulsa Plastik Hitam Perak dan Bentuk Bedengan terhadap Pertumbuhan Cabai Merah (Capsicum annuum L.) - Andri Sutiawan; Uun Sumarno (PT ADRIANI MANDIRI PUBLISHER, 2026)
Red chili pepper (Capsicum annuum L.) is one of the most economically important horticultural commodities and is continuously demanded by the community. One of the major challenges in chili cultivation, particularly during the dry season, is the increase in soil temperature and the decrease in soil moisture, which lead to greater water loss through evaporation. These conditions can inhibit plant growth and reduce crop productivity. One approach to improving the field microclimate is the use of silver-black plastic mulch combined with an appropriate bed configuration. This study aimed to analyze the effect of silver-black plastic mulch applied to different bed configurations on the growth of red chili pepper plants. The research was conducted at Afdeling II Plantation, Bilah Barat District, Labuhanbatu Regency, from October 2021 to April 2022. The experiment employed a Randomized Complete Block Design (RCBD) with a single factor consisting of four treatments and five replications, resulting in a total of 20 experimental units. The results showed that the application of silver-black plastic mulch with different bed configurations significantly affected plant height, number of leaves, and leaf area at 4, 6, and 8 weeks after planting (WAP). The best performance was obtained from the treatment using silver-black plastic mulch on flat planting beds, which produced average plant heights of 21.00 cm at 2 WAP, 40.25 cm at 4 WAP, 53.88 cm at 6 WAP, and 65.92 cm at 8 WAP. This treatment also resulted in the highest number of leaves, with averages of 10.85 leaves at 2 WAP, 30.80 leaves at 4 WAP, 87.25 leaves at 6 WAP, and 113.15 leaves at 8 WAP. Therefore, the use of silver-black plastic mulch on flat planting beds is recommended as an effective cultivation technique to enhance the vegetative growth of red chili pepper plants.